The effects of Fama-French five factor and momentum factor on Islamic stock portfolio excess return listed in ISSI - U’um Munawaroh; Sunarsih Sunarsih (Jurnal Ekonomi dan Keuangan Islam, 2020)
Purpose – The purpose of this study is to examine the effect of Fama-French five-factor and momentum factor on Islamic stock portfolio excess returns listed in the Indonesia Sharia Stock Index (ISSI).